(untitled) (Actualizaciones en Sida e Infectología, 2025)
Cryptogenic liver abscess (CLA) caused by hypervirulent Klebsiella pneumoniae (hvKp) is an endemic disease in Asia, and is rarely reported in Argentina. It affects healthy community members, leading to severe metastatic complications. hvKp strains predominantly belong to sequencetype ST23, capsular serotype K1, and to a lesser extent to other sequence types, K1 or K2. They usually possess plasmids carrying virulence genes involved in increased capsular production and siderophore biosynthesis. The hypermucoviscous (HMV) phenotype, together with broad antimicrobial susceptibility, are suggestive of hvKp, and the detection of genetic markers confirms it. We describe here the first report of hvKp-HMV ST375 (K2) causing CLA in this region. Rapid detection of hvKp associated with CLA allows for timely treatment, prevention of metastasis, and alerts about the global circulation of this emerging pathogen. Key words: hypervirulent Klebsiella pneumoniae, siderophore, liver abscess, sequencetype ST375.